IMPROVING STUDENTS’ READING THROUGH COMIC STRIPS MEDIA IN WEBTOON APPLICATION - Luluk Suryani; Mariyatul Kiptiyah; Chairuddin Chairuddin (Universitas Madura, 2023)
The aims of this research is to improve the students’ reading skill of the Tenth grade of SMAN 4 Bangkalan by using comic strips in webtoon application. This research is collaborative classroom action research. It aimed to discover and put into action various reading skills improving measures. The research procedure was an action research that consisted of four key phases: planning, implementing/ acting, observing, and reflecting. The researcher and teacher collaboratively recognized certain obstacles andweaknesses of the reading learning process, identified some problems, and planned and carried out the proposed actions. The result of the cycle shows that the implementation of comic strip improves the students’ reading skill, especially understanding the content of the text, vocabulary mastery, and motivation to read by providing the students kinds of reading activities. The success indicator of the implementation were that (1) the students were able to understand the content of the English text, by finding the main idea and specific information, (2) the students were more enthusiastic in doing reading activities, and (3) the students vocabulary mastery was improved. Furthermore, the findings were also supported by the means of the students’ reading score which improved from 62 in preliminary test to 76 in cycle test.